Macroeconomic effects of an energy saving policy in the public sector - Philippe Quirion (Fondazione Eni Enrico Mattei (FEEM), 2002)
Nearly all the macroeconomic literature on environmental policies deals with taxes and tradable permits. A policy instrument that still needs to be looked at is a switch in government expenditure away from environmentally-damaging goods, in particular fossil fuels, and toward resource- and energy-saving expenditure.
Keywords: E62; H57; Q38; 330; Resource conservation; energy conservation; public spending; employment; general equilibrium; multi-sectors models; Energieeinsparung; Öffentlicher Sektor; Öffentliche Ausgaben; Theorie; Makroökonomischer Einfluss